The Australian Army Uniform and the Government Clothing Factory Innovation in the Twentieth Century - van Mosseveld, Anneke (Springer International Publishing, 2018)
This book reveals the business history of the Australian Government Clothing Factory as it introduced innovative changes in the production and design of the Australian Army uniform during the twentieth century. While adopting a Schumpeterian interpretation of the concept of innovation, Anneke van Mosseveld traces the driving forces behind innovation and delivers a comprehensive explanation of the resulting changes in the combat uniform. Using an array of archival sources, this book displays details of extensive collaborations between the factory, the Army and scientists in the development of camouflage patterns and military textiles. It uncovers a system of intellectual property management to protect the designs of the uniform, and delivers new insights into the wider economic influences and industry linkages of the Government owned factory.